New insights into the phylogenetic relationships, character evolution, and phytogeographic patterns of Calceolaria (Calceolariaceae) - Cosacov Martinez, Andrea (2009)
Biogeographical patterns and diversification processes in Andean and Patagonian flora are not yet well understood. Calceolaria is a highly diversified genus of these areas, representing one of the most specialized plant - pollinator systems because flowers produce nonvolatile oils, a very unusual floral reward. Phylogenetic analyses with molecular (ITS and matK) and morphological characters from 103 Calceolaria species were conducted to examine relationships, to understand biogeographic patterns, and to detect evolutionary patterns of floral and ecological characters. Total evidence analysis retrieved three major clades, which strongly correspond to the three previously recognized subgenera, although only subgenus Rosula was retrieved as a monophyletic group. A single historical event explains the expansion from the southern to central Andes, while different parallel evolutionary lines show a northward expansion from the central to northern Andes across the Huancabamba Deflection, an important geographical barrier in northern Peru. Polyploidy, acquisition of elaiophores, and a nototribic pollination mechanism are key aspects of the evolutionary history of Calceolaria. Pollination interactions were more frequently established with Centris than with Chalepogenus oil-collecting bee species. The repeated loss of the oil gland and shifts to pollen as the only reward suggest an evolutionary tendency from highly to moderately specialized pollination systems.